Penentuan Teknologi Proses Pembuatan Gambir Murni dan Katekin Terstandar dari Gambir Asalan - Gustri Yeni; Khaswar Syamsu; Etik Mardliyati; Hendri Muchtar (Jurnal Litbang Industri, 2017)
Uncaria gambir Roxb. is an industrial crop commodity that has a high economic value and good prospect for farmers and exporter. Gambier of traditional processed products (raw gambier) generally have various catechin content, so it is required further handling to increase the purity of catechins from raw gambier. The research was aimed to get a process technology on the making of pure gambier and standardized catechins. Sources of raw materials was obtained from extraction process through steaming leaves and twigs of gambier (KA) using equipment from aluminum (RA) and from iron (RF). Purification of raw gambier through repeated extraction with water could decrease tannin content from 24% to 2.4% and increase catechin levels between 40% to 74%. Gambier with a low tannin content (catechin KA) through re-extraction using water had the highest increase of catechin content with a color of yellowish white product. The iron-containing equipment affected the color of the pure gambier produced, which was reddish-brown. The effect of solvent on further extraction using ethyl acetate solvent resulted in higher catechin content (up to 99%) compare to ethanol (95%). The catechin purity of KA samples was tested by looking at its stability at varying levels of acidity, showing catechins of gambier was stabile at pH 6.ABSTRAK Uncaria gambir Roxb. merupakan komoditas tanaman industri yang memiliki nilai ekonomi tinggi serta mempunyai prospek cukup baik bagi petani dan pemasok negara-negara asing. Gambir hasil olahan tradisional (gambir asalan), umumnya memiliki kandungan katekin yang beragam, sehingga diperlukan penanganan lebih lanjut untuk meningkatkan kemurnian katekin dari gambir asalan. Tujuan penelitian adalah untuk mendapatkan teknologi proses pembuatan gambir murni dan katekin terstandar. Sumber bahan baku diperoleh dari proses ekstraksi melalui pengukusan daun dan ranting tanaman gambir (KA) menggunakan peralatan dari aluminium (RA) dan dari besi (RF). Pemurnian gambir asalan melalui ekstraksi berulang dengan air dapat menurunkan kadar tanin, yaitu dari 24% sampai 2,4% dan meningkatkan kadar katekin, yaitu antara 40% sampai 74%. Gambir dengan kandungan tanin rendah (katekin KA) melalui ekstraksi ulang menggunakan air memiliki peningkatan kadar katekin tertinggi dengan warna produk putih kekuningan. Peralatan mengandung besi berpengaruh terhadap warna dari gambir murni yang dihasilkan, yaitu berwarna coklat kemerahan. Pengaruh pelarut terhadap ekstraksi lanjut menggunakan pelarut etil asetat menghasilkan kadar katekin lebih tinggi (sampai 98%) dibandingkan etanol (95%). Kemurnian katekin sampel KA diuji dengan melihat stabilitasnya pada berbagai tingkat keasaman, menunjukkan katekin dari gambir stabil pada pH 6.